The Digital Era and Teens: Analyzing the Influence of Multimedia on Social Media - Maulidina, Alisia; Maulani , Widya; Purnomo, Hendri (Secure And Knowledge-Intelligent Research in Cybersecurity And Multimedia (SAKIRA), 2024)
In this era of globalization technology is more advanced, it can’t be denied the presence of the internet more needed in everyday life, both in socialization, education, business, etc. We can’t be denied that social media have a big influence in our life. Someone who initially small can be great with social media, or otherwise. For the community particularly among teenagers, social media have to make opium user gone days without opening a social media. While in a fact, teenagers in school trying to find his identity with his feers hang out together with friends .This research aims to understand the influence of social media explained about what course the influence of social media for teenagers in century it has since then to know what course the influence on teen behavior caused by the current social media During the research, researchers used a method of the qualitative study because want to learn about a fact; symptoms and events the influence of social media against teen behavior in the field just as there are in the context of space and time as well as environmental situation teenagers naturally. Researchers wanting the results of research in the form of the data that is even more complex on the phenomena that is difficult expressed by a method of quantitative and do not need processing data is statistics. The result of the qualitative study required researchers is in the form of deep information about the influence of social media for teenagers itself.